Special economic zones in South Asia : structural change, competitiveness and growth - Aggarwal, Aradhna (Routledge, Taylor & Francis Group, 2024)
"Growth enhancing structural change - a relocation of labor from low to high productivity sectors is increasingly perceived as inextricably linked with the sustainable development agenda. In the pursuit of structural change, policy makers have pinned their hopes on targeted policy tools such as Special Economic Zones (SEZs). These geographically demarcated spaces designed to attract investment with a wide set of advantages have become de rigueur, however, a systematic evaluation of evidence-informed policy making is scarce due to conceptual and practical challenges. This book fills that gap and shows that the SEZs are no 'shortcut' to economic development but need to be re-strategized to address the emerging challenges. The first part of the book adopts an interdisciplinary approach to examine the links between SEZs and structural change, with a focus on South Asia, and develops an integrated conceptual framework for policy evaluation. Part 2 presents an empirical analysis of historical trends in growth and structural change in the eight regional economies under examination. Part 3 investigates the socioeconomic and cultural contexts in which the SEZs are embedded, assesses the fit between the SEZ goals and broader development strategies, and evaluates the SEZ policy design fit with the goals. The fourth part of the book presents counterfactual evaluation of the impact of SEZs on investment climate; export competitiveness of firms; technology and innovation; and knowledge linkages of SEZ firms with the wider economy, while the final part discusses the emerging challenges and the way forward. This will be a useful reference for academics, researchers, policymakers and professionals in international trade and business, public policy, industrial economics and regional integration"-- Provided by publisher.
Keywords: Free ports and zones -- South Asia.; Economic development -- South Asia.; South Asia -- Economic conditions.; elektronické knihy; electronic books